Species composition, abundance and distribution of butterflies in a home garden habitat located at Hanguranketha, Nuwara Eliya district, Sri Lanka - Rathnayake, R.R.M.U.N.B.; Karunarathna, D.S.; Dammini Premachandra, W.T.S. (University of Jaffna, 2023)
The species richness, abundance and distribution of butterflies associated with a home garden, which was comprised of three micro-habitats; a grassland [GL], shrubland [SL] and disturbed-forest [DF], at Hanguranketha region, Nuwara Eliya district, was determined for a period of four months from September to December 2021, using a visual encounter survey. At each habitat, a belt transect (100 m x 10 m) was set up, and weekly observations were made within 20 minutes in the morning and the afternoon. Species diversity and the evenness were estimated using the Shannon-Weiner diversity index. A total of 32 species representing five families, Hesperiidae, Lycaenidae, Nymphalidae, Papilionidae and Pieridae were encountered. Two species were reported as endangered, while 10 were endemic sub-species. These families were observed in all the three habitats, with the exception of Papilionidae in the GL. Nymphalidae was the most diverse family in DF (35 %) and SL (48 %) whereas Lycaenidae and Nymphalidae made up the most diversity in the GL (37 %). The DF harbored the highest species richness (88 %) and GL had the lowest (34 %). Altogether, 873 individuals were detected over four months. The abundance was found to be similar (P>0.05) in the DF and SL, but lower (P<0.05) in the grassland compared to the other two habitats. The maximum relative abundance was detected (61 %) in the Nymphalidae, while Hesperiidae showed the second highest abundance. The highest diversity (H=2.91) was recorded in the DF with 0.876 in evenness. Butterfly counts in the morning hours outnumbered the evening hours (P<0.05). A reduction in butterfly counts (P<0.05) was detected during November and December. The findings of this study revealed that this home garden is rich in butterflies and proper conservation mechanisms are essentially needed to protect them.
Keywords: Species richness; Abundance; Butterflies; Diversity; Habitats; Species richness